Changes in the Recruitment and Education of the Power Elites in Twentieth Century Western Democracies - Elise S. Brezis; François Crouzet (Bar-Ilan University, Department of Economics, 2002)
The aim of this paper is to examine the evolution of recruitment of elites and to investigate the nature of the links between recruitment and training of elites and economic development. We show that there was a key shift at the turn of the nineteenth century in the way the Western world trained its elites, with a second shift taking place after World War II, when meritocracy became the basis for recruitment of elites. Although meritocratic selection should result in the best being chosen, we show that meritocratic recruitment leads to class stratification and auto-recruitment. We analyze whether stratification resulting from meritocratic selection is optimal for the development of a country, and show that it is dependent on the type of technological changes occurring in the country.
Keywords: P2; 330; elite; auto-recruitment; training; education; meritocracy; stratification; economic growth